Exploring the Impact of TikTok and Social Media Addiction on Bedtime Procrastination Among High School Students - Selviana Selviana; Lida Maulida; Fidawsyi Nuzula (International Journal of Advanced Health Science and Technology, 2024)
Sleep is crucial for the body because it can improve the immune system and help teenagers concentrate at school. Meanwhile, each person's average sleep time is different. The standard sleep time for teenagers is 8 to 9 hours at night. The aspect that causes bedtime procrastination is self-restraint. Poor self-control can make a person's desire to sleep on time-inconsistent or unfulfilled. This research aims to analyze the relationship between TikTok and social media addiction among students at SMA. The population in this study was 83 and used random sampling techniques with questionnaire research instruments. The results of statistical tests using chi-square showed a significant value, namely p-value 0.007 > α 0.05, so there is a relationship between addiction to social media TikTok and bedtime procrastination in students at SMA X. It is hoped that this research can make students understand better the pros and cons of delaying bedtime. There needs to be increased health promotion counseling regarding the impact of excessive addiction to the social media TikTok, and schools and parents can set rules or limits on gadget use. In future researchers, it is expected that they can add related variables that influence addiction to social media TikTok and reduce bedtime procrastination (delayed sleep time).